School dropout in two secondary schools in Zvimba district area - Maseve, Primrose Tracy (Midlands State University, 2018)
The study was aimed at finding the factors leading to secondary school dropout and the strategies that can be used to reduce or eliminate school dropout. The descriptive survey research design was used. Purposive sampling was used to select 30 participants who participated in the study. These included 20 learners, 8 teachers and 2 school heads who all responded to the survey questionnaires. Questionnaires were used in data collection. The research findings showed that there are many aspects in life that contribute towards secondary school dropouts, particularly in rural areas. The major ones being poverty, financial constraints, long distance to and from school, low level of education for parents and personal behaviors amongst the learners. Also, strategies that can assist in reducing high secondary school dropout rate include financial assistance, poverty relief actions or plans, constructing more schools mostly in rural areas and introducing Guiding and Counselling or Peer education. The researcher concluded that secondary school dropout is a result of a number of factors and to reduce or eliminate the dropout rate, financial assistance should be given and both parents and learners should be educated on the importance of education. The researcher recommended that, parents or guardians should at all cost participate in the school activities of their children and both the school and the government should work towards improving learning and prevent school dropout.